2021
DOI: 10.1155/2021/6675762
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Impaired Autophagy in Fatty Liver Disease and Hepatocellular Carcinoma

Abstract: Autophagy is a conserved catabolic process that eliminates dysfunctional cytosolic biomolecules through vacuole-mediated sequestration and lysosomal degradation. Although the molecular mechanisms that regulate autophagy are not fully understood, recent work indicates that dysfunctional/impaired autophagic functions are associated with the development and progression of nonalcoholic fatty liver disease (NAFLD), alcoholic fatty liver disease (AFLD), and hepatocellular carcinoma (HCC). Autophagy prevents NAFLD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 163 publications
(256 reference statements)
1
37
0
Order By: Relevance
“… 19 Chronic exposure to viral and non-viral agents induces an integrated stress response which changes the cellular plasticity and cell fate. 10 , 54 At present many oncogenic processes have been implicated in HCC development including loss of tumor suppressors, angiogenesis, the immunosuppressive microenvironment in cirrhotic liver, inflammation, epigenetics modifications, and cancer stem cells. In addition, emerging new evidence indicates that angiogenesis and immunosuppressive microenvironment are frequently involved in HCC development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Chronic exposure to viral and non-viral agents induces an integrated stress response which changes the cellular plasticity and cell fate. 10 , 54 At present many oncogenic processes have been implicated in HCC development including loss of tumor suppressors, angiogenesis, the immunosuppressive microenvironment in cirrhotic liver, inflammation, epigenetics modifications, and cancer stem cells. In addition, emerging new evidence indicates that angiogenesis and immunosuppressive microenvironment are frequently involved in HCC development.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Furthermore, impairment of autophagy leads to hepatocellular carcinoma (HCC) development in several animal models and this effect has been demonstrated in cirrhotic livers with HCC. 9 , 10 Liver-specific deletion of autophagy genes (ATG5 or ATG7) caused a spectrum of hepatic diseases including steatosis, inflammation, fibrosis, hepatomegaly, and HCC. 11 , 12 Moreover, impaired autophagy promotes tumorigenesis in Beclin1 or LkB1 gene knockout mice livers.…”
Section: Introductionmentioning
confidence: 99%
“…However, large or chronic lipid exposure tends to deregulate the autophagy process [13,[16][17][18]. Accumulating evidence suggests that impaired autophagy prevents the clearance of LDs, damaged mitochondria, and toxic protein aggregates, which can be produced during the progression of various liver diseases, thus contributing to the development of steatosis, steatohepatitis, fibrosis, and cancer [19,20]. This supports the possibility that autophagy may be one of the key targets for the prevention and treatment of hepatic steatosis in NAFLD [21].…”
Section: Introductionmentioning
confidence: 86%
“…Activating autophagy via increased AMPK phosphorylation, decreased mTOR, and increased LC3B expression [ 108 ]. Autophagy can prevent NAFLD and AFLD progression through enhanced lipid catabolism and decreased hepatic steatosis [ 109 ]. Our study observed the expression of p62 that actually appears to play a negative regulatory role in autophagy, and p62 accumulation is observed in the liver of ob/ob mice, and its aggregation is correlated with serum ALT activity and inflammatory activity by the NAFLD score [ 110 ].…”
Section: Discussionmentioning
confidence: 99%